2021
DOI: 10.1007/s11356-021-16741-x
|View full text |Cite
|
Sign up to set email alerts
|

Cold plasma technology: advanced and sustainable approach for wastewater treatment

Abstract: Cold plasma has been a potent energy-efficient and eco-friendly advanced oxidation technology which has gained attention in recent decades as a non-thermal approach in diverse forms of applications. This review highlights a comprehensive account of the implementation of this technology in the field of wastewater treatment to resolve certain issues regarding the degradation of numerous aqueous pollutants and water-borne pathogenic microorganisms including viruses up to a significant level. The paper addresses p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 102 publications
0
28
0
Order By: Relevance
“…In juices, cold plasma technology leads to the degradation of extremely polymerized oligosaccharides [146], which is caused by ozonolysis. The high consumption of gas is also cited as a limitation or drawback of the technology [147], especially for large-scale applications. Furthermore, the high cost of setting up the cold plasma technology tends to be a major challenge or drawback.…”
Section: Cold Plasma For Industrial Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In juices, cold plasma technology leads to the degradation of extremely polymerized oligosaccharides [146], which is caused by ozonolysis. The high consumption of gas is also cited as a limitation or drawback of the technology [147], especially for large-scale applications. Furthermore, the high cost of setting up the cold plasma technology tends to be a major challenge or drawback.…”
Section: Cold Plasma For Industrial Applicationmentioning
confidence: 99%
“…Studies have demonstrated the potential and application of cold plasma technology in the decontamination of wastewater. Cold plasma decontamination lowers the amount of pollutants in wastewater [147]. Furthermore, treatment with cold plasma reduced several water-borne pathogenic microorganisms [46, [148][149][150][151] revealed the substantial inactivation of spike protein in plasma inactivated water to inhibit coronavirus transmission.…”
Section: Cold Plasma For Industrial Applicationmentioning
confidence: 99%
“…As a result, understanding the parameters that influence NTP’s antiviral efficacy is critical. Numerous studies have found that several parameters substantially impact the effectiveness of NTP (Bermudez-Aguirre 2019 ; Gururani et al 2021 ). These parameters are essential in the inactivation of viruses.…”
Section: Parameters Controlling the Viruses’ Inactivation Using Non-t...mentioning
confidence: 99%
“…It is widely utilized because it may inactivate harmful microorganisms at room temperature without wasting energy in heating the background gas (Assadi et al 2021 ). It has been proven to remediate contaminated surfaces safely and efficiently at atmospheric pressure and room temperature (Gururani et al 2021 ). A variety of techniques can be used to create cold plasma, such as DBD and corona discharges (CD) (Van Nguyen et al 2019 ; Domonkos et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation